DETEKSI KOMUNITAS BAKTERI PADA DIAPHORINA CITRI JANTAN DAN BETINA, VEKTOR PENYAKIT HUANGLONGBING PADA JERUK MENGGUNAKAN PCR-RISA - Achmad Himawan; Siti Subandiyah (AGROISTA : Jurnal Agroteknologi, 2017)
Huanglongbing (HLB) is a very destructive disease on citrus. Diaphorina citri is a HLB disease vector. The aim of this research is to detec bacterial community in the insect vector, especially D. citri males and females, using Polimerase Chain Reaction-Ribosomal Intergenic Spacer Analysis (PCR-RISA) method. The results of research show that there are 3 – 4 bacteria species in D. citri males and 1 – 4 bacteria species in D. citri females.